QP-ChainSZKP: A Quantum-Proof Blockchain Framework for Scalable and Secure Cloud Applications - V. Ananthakrishna; Chandra Shekhar Yadav (International Journal of Computational and Experimental Science and Engineering, 2025)
In the rapidly evolving landscape of cloud computing, the burgeoning growth and centralization of data exacerbate security vulnerabilities, necessitating robust and scalable cryptographic solutions. This paper introduces the QP-ChainSZKP framework, a novel architecture that amalgamates Quantum-Secure Cryptographic Algorithms with Zero-Knowledge Proof Management to shield cloud environments against both classical and emerging quantum threats. The proposed QP-ChainSZKP framework effectively integrates advanced cryptographic techniques, enhancing the security protocols and compliance measures required for robust cloud operations. This ensures not only adherence to high-security standards but also provides strong protection against data breaches and unauthorized access, crucial for maintaining data integrity and confidentiality in cloud environments. We employ a dual approach in our methodology by simulating and rigorously testing the framework to evaluate its security, scalability, and performance metrics. The experimental results demonstrate a significant enhancement in transaction throughput and reduction in latency, corroborating the framework’s capability to manage high throughput cloud applications effectively. Specifically, the framework achieves a throughput improvement of 20% and a latency reduction of 30% under peak load scenarios, establishing its efficacy in handling dynamic cloud environments. Notably, the QP-ChainSZKP framework addresses future quantum computational threats by modifying existing cryptographic practices used in public clouds, setting a pioneering standard for using advanced cryptographic technologies in cloud security. Our study contributes a scalable, quantum-resistant solution tailored for extensive cloud applications, marking a substantial advancement in cloud computing security frameworks that can meet the imminent global security requirements.